Polityka konkurencji a spójność gospodarcza i społeczna w Unii Europejskiej - Korbutowicz, Teresa (Competition Policy and Economic and Social Cohesion, 2006)
The European competition policy is used to attain the goals of integration such as the development of a uniform internal market, to stimulate the competitiveness of different member states' economies and to ensure a social and economic cohesion. The competition policy is closely linked to other economic policies both at the EC level and national levels. Competition is protected through the established principles of law, interpretation and decisions of associations of undertakings, abuse of a dominant position by one or more undertakings, concentrations of undertakings and public aid are all subject to examination and inspection with a focus on how they may affect internal trade and constrain competition. The cohesion policy is related to the economic growth and increase of the competitiveness of the international Community. New programmes are to concentrate on regional convergence, competitiveness and employment as well as regional partnerships. In view of the above goals of the cohesion policy under the competition policy, it is essential that barriers should be moved and an internal market be created. One of the methods to serve the purpose is liberalisation of regulated sectors, namely: telecommunication, transport, mail service and power supply, which is expected to benefit the growth of competition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 83-92